2008
DOI: 10.1001/archderm.144.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study of Pegylated Liposomal Doxorubicin Treatment in Patients With Advanced or Refractory Mycosis Fungoides or Sézary Syndrome

Abstract: To assess the rate of objective response to pegylated liposomal doxorubicin hydrochloride (Caelyx) in patients with advanced or refractory cutaneous T-cell lymphoma (CTCL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 45 publications
2
36
1
5
Order By: Relevance
“…For example, overall response rates of 58-76% (and 41% complete response rate) have been observed in patients with MF/SS treated with low-dose, oral methotrexate [336][337][338][339]. In contrast, for patients with an adequate performance status, single-agent gemcitabine [340][341][342][343][344], pegylated liposomal doxorubicin [345][346][347][348] and pentostatin [349][350][351][352][353][354][355] are frequently utilized (Table VI). Gemcitabine, a pyrimidine nucleoside analog, is associated with overall and complete response rates of 50-70% and 10-20%, respectively, but is associated with neutropenia and nonhematologic toxicities [356].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, overall response rates of 58-76% (and 41% complete response rate) have been observed in patients with MF/SS treated with low-dose, oral methotrexate [336][337][338][339]. In contrast, for patients with an adequate performance status, single-agent gemcitabine [340][341][342][343][344], pegylated liposomal doxorubicin [345][346][347][348] and pentostatin [349][350][351][352][353][354][355] are frequently utilized (Table VI). Gemcitabine, a pyrimidine nucleoside analog, is associated with overall and complete response rates of 50-70% and 10-20%, respectively, but is associated with neutropenia and nonhematologic toxicities [356].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…Overall, seven of nine complete responders remained in continuous complete remission with a diseasefree interval ranging from 15 months to 10 years. In the largest prospective study of pegylated liposomal doxorubicin, an overall response rate of 56%, with a complete response rate of 20%, was reported [348]. Pegylated liposomal doxorubicin is generally well tolerated, with a lower incidence of neutropenia than gemcitabine, but with occasional infusion-related and mucocutaneous toxicities, including palmoplantar erythrodysesthesia.…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…Thus, in patients with relatively slowly progressive disease who have failed other treatments, we would consider low-dose oral MTX, chlorambucil, cyclophosphamide, or etoposide. For patients with more rapidly progressive disease and of reasonable performance status, our preference is to use single-agent gemcitabine, 63,[93][94][95] pentostatin, 54,64,[96][97][98][99][100] or liposomal doxorubicin 65,101,102 as these agents have been investigated the most thoroughly. Gemcitabine has a high response rate, but myelosuppression can be problematic with dose-reduction frequently required.…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…ComPharmacodynamic and pharmacokinetic study of pegylated liposomal doxorubicin combination (CCOP) chemotherapy in patients with peripheral T-cell lymphomas www.chinaphar.com Fan Y et al Acta Pharmacologica Sinica npg pared to conventional doxorubicin injection, PLD has a longer retention time in blood circulation, lower cardiotoxicity and improved targeted efficiency [8] . Recently, there have been several clinical studies on PLD-based NHL treatment that have shown it to be superior in the treatment of the elderly or patients with primarily cutaneous T-cell lymphomas (CTCL) with aggressive NHL [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%